GA document 119 :. (Tokyo : A.D.A. edita, 2011)
- Zaha Hadid: CMA CGM Tower, Marseille, France##- Zaha Hadid: Maggie's Gartnavel, Glasgow, U.K.##- OMA: Expansion of MNBAQ/Musee National des Beaux-Arts du Quebec, Quebec City, Canada##- OMA: Stadskantoor Rotterdam, Rotterdam, The Netherlands##- Enric Miralles Benedetta Tagliabue/EMBT: Youth Music School and Auditorium (extension), Hamburg, Germany##- Morphosis: Vialia Vigo, Vigo, Spain##- Jean Nouvel: Frasers Broadway Residences and Serviced Apartments, Sydney, NSW, Australia##- Norman Foster: Hermitage Towers, Paris, France##- Renzo Piano: Valletta City Gate, Valletta, Malta##- Renzo Piano: Kimbell Art Museum Expansion, Fort Worth, Texas, U.S.A.##- Coop Himmelblau: Martin Luther Church Hainburg, Hainburg, Austria##- Ryue Nishizawa: Hiroshi Senju Museum Karuizawa, Nagano, Japan
boek
Keywords: Tagliabu, Benedetta; Oma; Miralles, Enric; Hadid, Zaha; Morphosis; Nouvel, Jean; Foster, Norman; Piano, Renzo; Himmelblau, Coop; Nishizawa, Ryue